Niemann–Pick Disease Type C: Induced Pluripotent Stem Cell–Derived Neuronal Cells for Modeling Neural Disease and Evaluating Drug Efficacy. (September 2014) - Yu, Daozhan; Swaroop, Manju; Wang, Mengqiao; Baxa, Ulrich; Yang, Rongze; Yan, Yiping; Coksaygan, Turhan; DeTolla, Louis; Marugan, Juan J.; Austin, Christopher P.; McKew, John C.; Gong, Da-Wei; et al.
Niemann–Pick disease type C (NPC) is a rare neurodegenerative disorder caused by recessive mutations in the NPC1 or NPC2 gene that result in lysosomal accumulation of unesterified cholesterol in patient cells. Patient fibroblasts have been used for evaluation of compound efficacy, although neuronal degeneration is the hallmark of NPC disease. Here, we report the application of human NPC1 neural stem cells as a cell-based disease model to evaluate nine compounds that have been reported to be efficacious in the NPC1 fibroblasts and mouse models. These cells are differentiated from NPC1 induced pluripotent stem cells and exhibit a phenotype of lysosomal cholesterol accumulation. Treatment of these cells with hydroxypropyl-β-cyclodextrin, methyl-β-cyclodextrin, and δ-tocopherol significantly ameliorated the lysosomal cholesterol accumulation. Combined treatment with cyclodextrin and δ-tocopherol shows an additive or synergistic effect that otherwise requires 10-fold higher concentration of cyclodextrin alone. In addition, we found that hydroxypropyl-β-cyclodextrin is much more potent and efficacious in the NPC1 neural stem cells compared to the NPC1 fibroblasts. Miglustat, suberoylanilide hydroxamic acid, curcumin, lovastatin, pravastatin, and rapamycin did not, however, have significant effects in these cells. The results demonstrate that patient-derived NPC1 neural stem cells can be used as a model system for evaluation of drug efficacy and study of disease pathogenesis.